2020
DOI: 10.1155/2020/2367505
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Combined Radial Endobronchial Ultrasound-Guided Transbronchial Lung Biopsy and Metagenomic Next-Generation Sequencing for Peripheral Pulmonary Infectious Lesions

Abstract: Background. Metagenomic next-generation sequencing (mNGS) is a new technology that allows for unbiased detection of pathogens. However, there are few reports on mNGS of lung biopsy tissues for pulmonary infection diagnosis. In addition, radial endobronchial ultrasound (R-EBUS) is widely used to detect peripheral pulmonary lesions (PPLs), but it is rarely used in the diagnosis of peripheral lung infection. Objective. The present study aims to evaluate the combined application of R-EBUS-guided transbronchial lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…By analyzing the content and abundance of DNA or the RNA of microorganisms in clinical samples, this technology could be used to determine the pathogenic bacteria and was successfully applied to identify the pathogens from patients' BALF or lung tissue samples. [25][26][27][28] Importantly, the sensitivity of using mNGS to diagnose infectious diseases was higher than conventional culture, especially for bacteria that are difficult to cultivate, such as anaerobes. 29,30 Moreover, mNGS is less affected by antibiotic exposure before sample detection, 29 and thus has more advantages in detecting the co-infection of multiple bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the content and abundance of DNA or the RNA of microorganisms in clinical samples, this technology could be used to determine the pathogenic bacteria and was successfully applied to identify the pathogens from patients' BALF or lung tissue samples. [25][26][27][28] Importantly, the sensitivity of using mNGS to diagnose infectious diseases was higher than conventional culture, especially for bacteria that are difficult to cultivate, such as anaerobes. 29,30 Moreover, mNGS is less affected by antibiotic exposure before sample detection, 29 and thus has more advantages in detecting the co-infection of multiple bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the TBLB mNGS provides more accurate diagnostic results, while the hard-to-obtain specimens should be diagnosed using BALF sampling methods. A study showed that the positive rate of TBLB mNGS guided by R-EBUS (78.7%) was significantly higher than that of the TBLB group (60.0%), because R-EBUS significantly improved the accuracy of bronchoscopy in obtaining lesion specimens ( Li et al., 2020 ). ROSE is a rapid cytological evaluation technology that can be used for tissue sample collection ( Ganc et al., 2015 ).…”
Section: Influence Of Different Sampling Methods On the Detection Efficiency Of Mngsmentioning
confidence: 99%
“…The establishment of localized experimental platforms can even provide valid etiological information within 10-24 hours. In addition, as an unbiased detection method, mNGS can simultaneously detect a diverse range of microorganisms, including bacteria, fungi, and viruses, in clinical specimens [4].…”
Section: Introductionmentioning
confidence: 99%